A study of clinical profile and treatment outcome in patients of liver abscess admitted in a tertiary care centre - Kishor, Anand; Kumar, Sudhir; Kumar, Ravikant (International Journal of Research in Medical Sciences, 2025)
Background: Liver diseases have a wide range of clinical implications. Commonly found to be pyogenic or amoebic in origin, fungi and parasites account for a small percent of cases. Liver abscesses have been linked to a mortality rate as high as 20%. Underdeveloped nations have greater rates of amoebic liver abscess (ALA). The study was performed to analyse the clinical manifestation and treatment outcome among patients with hepatic abscesses. Methods: It was a cross-sectional, observational study. The study took place for one year at Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India. Total 100 patients were enrolled into this study. Ethical clearance to conduct this study was obtained from Institutional Ethics Committee (IEC) of IGIMS, Patna, Bihar, India under letter no. 752/IEC/IGIMS/2022 dated 06 October 2022. Results: Average age in years of included participants was 42.82±11.33. Total 90 male participants were enrolled into the study and 10 female participants were part of the study. Forty-seven individuals with bilirubin levels above normal had clinical jaundice. Hemoglobin levels below 11 gm% were identified in 64 cases (64%), with the lowest recorded hemoglobin in this series being 6.7 gram%. The study determines an important statistically significant correlation (p value =0.000109) between the alcohol consumption and amoebic liver abscess. Conclusions: The study concluded that substantial statistical association between alcohol use and liver abscess. Single, isolated abscesses were more prevalent than multiple abscesses, and the right lobe of the liver was more frequently afflicted. The medical management therapy has been provided to all the patients.